2001
DOI: 10.1152/jappl.2001.91.2.596
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-1 receptor stimulation attenuates the vasoconstrictive response to gut ischemia

Abstract: The effects of fenoldopam, a dopamine-1 (DA-1) receptor agonist, were studied in two groups of anesthetized dogs before and after induction of splanchnic ischemia by way of hemorrhage. During the first portion of the experiment, both groups received fenoldopam (1.5 microg x kg(-1) x min(-1)) for 45 min followed by a 45-min washout. During the second portion, hemorrhage (10 ml/kg) was induced, followed by no intervention in group I (controls) and restarting of the fenoldopam infusion in group II. Prehemorrhage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…The observed increased gastric mucosal oxygenation during fenoldopam infusion was caused rather by increased microvascular Ḋ O 2 than by decreasing regional oxygen consumption. However, because we did not measure regional blood flow, it remains unclear if this was caused by an increase in total gastric perfusion or by an intramural redistribution of blood flow toward the gastric mucosa (31). The effects of fenoldopam were abolished by DA 1 -receptor blockade, implying that other vasodilatory mechanisms [e.g., ␣ 1 -antagonism as described for fenoldopam (12)(13)(14)] are negligible.…”
Section: Interpretation Of Resultsmentioning
confidence: 94%
“…The observed increased gastric mucosal oxygenation during fenoldopam infusion was caused rather by increased microvascular Ḋ O 2 than by decreasing regional oxygen consumption. However, because we did not measure regional blood flow, it remains unclear if this was caused by an increase in total gastric perfusion or by an intramural redistribution of blood flow toward the gastric mucosa (31). The effects of fenoldopam were abolished by DA 1 -receptor blockade, implying that other vasodilatory mechanisms [e.g., ␣ 1 -antagonism as described for fenoldopam (12)(13)(14)] are negligible.…”
Section: Interpretation Of Resultsmentioning
confidence: 94%
“…To increase splanchnic tissue oxygenation, catecholamines with activity on dopaminergic DA 1 -receptors, mediating mesenteric vasodilation, have been suggested (3). Moreover, since DA 1 -receptors are densely located in the vessels of the gastrointestinal mucosa compared with other layers, dopaminergics might facilitate intramural redistribution of perfusion toward the mucosa (3)(4)(5). In this context, dopamine has been used commonly, but its effectiveness has been questioned increasingly (6 -8).…”
mentioning
confidence: 99%
“…We (15) previously demonstrated that fenoldopam increases portal blood flow in a similar experimental model. The present study corroborates this effect and also demonstrates that this results in increased splanchnic Ḋ O 2 , which is expected from the augmentation in regional flow.…”
Section: Discussionmentioning
confidence: 66%
“…In a similar experimental model, we (15) showed that fenoldopam induces a redistribution of gut blood flow away from the serosa and favors the mucosa. Assuming that local perfusion is normally closely matched to local oxygen demands, this drug-induced redistribution could result in a less favorable perfusion heterogeneity and explains the increase in Ḋ O 2crit found for the overall splanchnic circulation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation